Cognitive profiles in euthymic patients with bipolar disorders: results from the FACE‐BD cohort. (19th April 2017) - Roux, Paul; Raust, Aurélie; Cannavo, Anne Sophie; Aubin, Valérie; Aouizerate, Bruno; Azorin, Jean‐Michel; Bellivier, Frank; Belzeaux, Raoul; Bougerol, Thierry; Cussac, Iréna; Courtet, Philippe; Etain, Bruno; et al.
Abstract : Objectives: Although cognitive deficits are a well‐established feature of bipolar disorders (BD), even during periods of euthymia, little is known about cognitive phenotype heterogeneity among patients with BD. Methods: We investigated neuropsychological performance in 258 euthymic patients with BD recruited via the French network of expert centers for BD. We used a test battery assessing six domains of cognition. Hierarchical cluster analysis of the cross‐sectional data was used to determine the optimal number of subgroups and to assign each patient to a specific cognitive cluster. Subsequently, subjects from each cluster were compared on demographic, clinical functioning, and pharmacological variables. Results: A four‐cluster solution was identified. The global cognitive performance was above normal in one cluster and below normal in another. The other two clusters had a near‐normal cognitive performance, with above and below average verbal memory, respectively. Among the four clusters, significant differences were observed in estimated intelligence quotient and social functioning, which were lower for the low cognitive performers compared to the high cognitive performers. Conclusions: These results confirm the existence of several distinct cognitive profiles in BD. Identification of these profiles may help to develop profile‐specific cognitive remediation programs, which might improve functioning in BD.